DESIGN OF A WEB-BASED INFORMATION SYSTEM FOR THE INDONESIAN METHODIST CHURCH ANTIOCH TEBING TINGGI - Dea Elisabet Indriani Siahaan; Roni Jhonson Simamora; Gortap Lumbantoruan (PT. MITRA ANGKASA INFORMATIKA, 2025)
Advances in information technology have a significant impact on various aspects of life, including the religious sphere. The Antioch Methodist Church of Indonesia still faces challenges in congregation data collection and information delivery due to its lack of an adequate information system. To address this issue, a website-based information system was developed that church administrators can use to manage congregation data and deliver information more effectively. This system helps speed up work processes, minimize errors, and improve the quality of service to the congregation and the general public. Furthermore, the system is designed to be easy to use and accessible at any time, thus supporting a more modern, transparent, and responsive church ministry to the congregation's needs. Keywords: system, information, information system, congregational data.